CRIMINAL AND LEGAL CHARACTERISTICS OF VIOLENCE IN ARTICLE 38 OF THE CRIMINAL CODE OF UKRAINE - KhramtsovOleкsandr (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2021)
The article gives a criminal-legal description of violence as a category of the General part of the legislation of Ukraine on criminal responsibility. The author’s definition of the concept of criminal violence is given in the work. It is emphasized that the latter characterizes the circumstances that exclude the criminal illegality of the act. According to the author, the meaning of violence in these circumstances is as follows: characterizes the factual and legal basis of the circumstances that exclude the criminal illegality of the act; the use of violence against a person is a ground for "unlimited" use of force for protection; in some cases, excessive use of force may lead to criminal responsibility. Special attention is paid to the criminal and legal characteristics of violence in Art. 38 of the Criminal Code of Ukraine. It is noted that the latter characterizes the legal basis of criminal detention of a person who has committed a criminal offense and determines the legality of such detention. It is reasonably stated that the legal basis for detention should be a socially dangerous infringement, but not a criminal offense. This approach will allow the application of the relevant criminal law norm to cases of such acts by persons who do not have the characteristics of the subject of the crime (have not reached the age of criminal responsibility or non compos). It is determined that the legal basis for detention is the committing of any socially dangerous act that has the characteristics of a criminal offense. Such conclusions are made on the basis of a systematic analysis of the current legislation of Ukraine on criminal responsibility. The author argues the erroneousness of the position establishing in the law an exhaustive list of criminal offenses, in the case of which criminal detention is possible. In his opinion, this is possible in case of committing any criminal offense. Based on the analysis of theoretical exploring in the relevant direction and the practice of application of criminal responsibility legislation, a reasonable conclusion is made that murder in excess of the limits of detention of a person who has committed a criminal offense can be committed with both direct and indirect intent. It is emphasized that the provisions of Art. 36 of the Criminal Code of Ukraine on taking into account the state of strong emotional excitement in the qualification of a person’s actions should be extended to cases of lawful detention by a person against whom a criminal offense was committed. The article provides the author’s version of Part 3 of Art. 38 of the legislation of Ukraine on criminal responsibility.